Market Needs Assessment for Bachelor of Science in Industrial Security Management in a State-Funded College - Patahlinghug, Mark Erana; Patahlinghug, Haidee F (Jurnal Pendidikan Progresif, 2021)
Market Needs Assessment for Bachelor of Science in Industrial Security Management in a State-Funded College. Objective: This study was carried out to evaluate and appraise the market demand for a Bachelor of Science in Industrial Security in J.H. Cerilles State College, Philippines in 2021. Methods: The methodology used for this study was a descriptive survey conducted online using google forms. A random sampling method was used in selecting the 100 respondents from among students, graduates, and professionals from private and public institutions. Frequency counts, percentage, and weighted average mean were used in analyzing the data. Findings: The result revealed that offering BSISM in JHCSC is feasible as to the management viability, market viability, operation viability, and location, as well as industry viability. Conclusion: Competent and qualified teachers and staff are required for the long-term viability of the new program offering, with the availability of teaching resources being a secondary consideration in the decision to offer such a program. Location and future demand must also be given attention prior to proposing a new course.Keywords: industrial security, security profession, market demand viability.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202111